1979
DOI: 10.1002/pssa.2210520127
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the magnetic moments in (Fe1–xMnx)3al alloys

Abstract: The average magnetic moment and the magnetic moments of the sublattices of (Fe1–xMnx)3Al alloys are determined from saturation magnetization and neutron diffraction. By Mössbauer experiments the effective magnetic fields on 57Fe nuclei are measured. The distribution of Fe, Mn, and Al on the three sublattices of the DO3 structure are determined by means of neutron and X‐ray diffraction. The observed decrease of magnetic moments with increasing Mn concentration is explained by the occurrence of parasitic antifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Indeed, it is known that when concentration of manganese in Fe 3-x Mn x Si exceeds x = 0.7, the manganese atoms start to occupy (A, C) positions in addition to the B-sites. This process takes place at even lower concentrations in Fe 3-x Mn x Al [9].…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, it is known that when concentration of manganese in Fe 3-x Mn x Si exceeds x = 0.7, the manganese atoms start to occupy (A, C) positions in addition to the B-sites. This process takes place at even lower concentrations in Fe 3-x Mn x Al [9].…”
Section: Introductionmentioning
confidence: 93%
“…Unfortunately, there are experimental facts that contradict such a simple picture. The preference of Mn to occupation of B-sites is not so clear in Fe 3 Al alloys [12,13]. In the case of chromium substituting for iron the number of experiments [14][15][16] showed that chromium does not show any preference in Fe 3 Si while there is certain preference to occupation of B-sites in Fe 3 Al.…”
Section: Introduction: Preferential Occupation Of Sitesmentioning
confidence: 99%
“…The alloy is a ferrimagnet with the magnetic moments at the Fe and Mn atoms equal to -0.16 and +2.32 μ B , respectively. Note that in the few experimental works [10][11][12][13][14] the results of calculations have not been con firmed in either the mutual orientation of the moments or in the magnitude of the magnetic moment per formula unit. The type of magnetic ordering also has not been determined.…”
Section: Introductionmentioning
confidence: 98%